A novel mononuclear complex of 4, 4″-azobis-(2, 2′-bipyridine) coordinated to tetracyanoruthenium(II) can behave as a "molecular switch". (1st December 2019) - Abate, Pedro O.; Pourrieux, Gaston; Morán Vieyra, Faustino E.; Borsarelli, Claudio D.; Parella, Teodor; Vergara, Mónica M.; Katz, Néstor E.
Graphical abstract: This is the first report of applications of spectral changes originated from a double proton-coupled electron transfer of an azo group in a bipyridyl ligand coordinated to tetracyanoruthenium(II) for molecular sensing purposes, in particular for detecting the biologically relevant analyte l -Cysteine. Abstract: A novel tetracyanoruthenium(II) complex of formula K2 [Ru(4, 4″-azobpy)(CN)4 ], (1 ), with 4, 4″-azobpy = 4, 4″-azobis-(2, 2′-bipyridine), has been synthesized and characterized by spectroscopic, electrochemical and photophysical techniques. The effects of reduction and protonation of the azo group of coordinated 4, 4″-azobpy in the UV–Vis absorption and emission spectra of (1 ) were explored by spectroelectrochemical techniques and by addition of l -Cysteine. The behavior of (1 ) as a "molecular switch" could be explained with the aid of quantum–mechanical calculations by using density functional theory.